Integrating Digital Tools and Learning Strategies to Enhance Speaking Proficiency: Evidence from a Mixed-Methods Study in Indonesian EFL Universities - Fitra Pinandhita (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
Advances in educational technology have changed the paradigm of English learning, especially in mastering speaking skills. This research departs from the need to integrate digital tools with language learning strategies in a structured manner to improve the speaking ability of EFL students in Indonesian universities. The novelty of this study lies in the mixed methods approach that associates quantitative data on the increase in speaking scores with the qualitative narrative of student learning experience, as well as focusing on advanced students (sixth semester) at three universities in Central Java. The purpose of this study is to analyze the extent to which the combination of digital technology and learning strategies can improve speaking skills, identify the most effective combinations of strategies, and understand students' perceptions and experiences of these applications. The study used a convergent parallel mixed methods design, involving 60–120 participants for quantitative data and 8–16 for qualitative data. Results showed significant improvements in fluency, accuracy, vocabulary, and pronunciation, with a large effect size (d > 0.8). Metacognitive strategies with MALL applications proved to be the most effective, followed by cognitive strategies on collaborative platforms and social-affective strategies through speech recognition tools.